Clinical comparison between Multi-Stranded Wires and Single strand Ribbon wires used for lingual fixed retainers - Valiollah Arash; Mehran Teimoorian; Yasamin Farajzadeh Jalali; Sedigheh Sheikhzadeh (SpringerOpen, 2020)
Abstract Background Long-term retention with fixed retainers with a high success rate seems to be a reasonable solution to minimize or prohibit relapse of orthodontic treatment. Methods Two hundred sixty patients between 13 and 30 years old were recruited for this study. The 0.0175 stainless steel twisted wire (G&H Orthodontics, USA) was compared with a single-strand ribbon titanium lingual retainer wire (Retainium, Reliance orthodontics, USA) was used. When treatment was completed, the retainers were bonded from canine to canine in the mandibular arch of the participants. In the follow-up visits, the patients were recalled every 3 months during the 24 months. Detachments, the time of debonding, and side effects were recorded. Statistical analysis was performed by a blinded statistician using a statistical package for Social Science (SPSS, Version20). After descriptive statistics, Kaplan-Meier analysis was performed to measure the survival rates of each retainer. P value < 0.05 was considered as significant. Results Finally, 138 patients who received twisted wire splint and 112 patients who received ribbon wire were included in the analysis. The average duration of success was about 23 months for twisted wire and ribbon wire, according to the Kaplan-Meier estimates. The analysis showed no significant overall difference between the treatments (p = 0.13). Failure rates in terms of detachments in all groups occurred at the enamel junction, and it was 25 in twisted retainer group (18.1%) and was 10 in ribbon retainer group (8.9%); the Kaplan-Meier analysis test detected a significant difference in the failure rates between the groups (p = 0/006). Conclusions Although the conventional twisted stainless steel wire and single-strand titanium flat metal ribbon wire as fixed orthodontic retainers have the same clinical effects, it was shown that the ribbon wire has less failure in terms of detachments.